2016
DOI: 10.11005/jbm.2016.23.2.95
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Muscle Mass Deficits Estimated from Bioelectrical Impedance Analysis and Lumbar Spine Bone Mineral Density in Korean Adults

Abstract: BackgroundBone mineral density (BMD) is influenced by many factors. Despite the reported association between body components and BMD, most of these studies investigated the relationship between absolute muscle mass or fat mass and BMD in postmenopausal women or elderly subjects. The aim of this study is to investigate the association between muscle mass deficits (MMD) estimated from bioelectrical impedance analysis (BIA) and lumbar spinal BMD in Korean adults 20 to 49 years of age.MethodsThis cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Muscle mass deficit was an independent risk factor for low BMD in healthy subjects. 34 Both lean mass and muscle strength were positively associated with BMD. 16 Sarcopenia was correlated with the BMD of patients with inflammatory bowel disease, chronic obstructive lung disease, and healthy subjects.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Muscle mass deficit was an independent risk factor for low BMD in healthy subjects. 34 Both lean mass and muscle strength were positively associated with BMD. 16 Sarcopenia was correlated with the BMD of patients with inflammatory bowel disease, chronic obstructive lung disease, and healthy subjects.…”
Section: Discussionmentioning
confidence: 95%
“…Chronic kidney disease was identified in 22 patients (20%) and diabetes mellitus in 25 patients (22%). The median handgrip strength was 32 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40) kg in men and 21 (17)(18)(19)(20)(21)(22)(23)(24)(25) kg in women. The median interval period between measurements of the ASMI and BMD was 35 (0-91) days.…”
Section: Baseline Characteristicsmentioning
confidence: 98%
“…Muscle mass is significantly associated with BMD and could be considered an independent risk factor for a low BMD in the general population and patients undergoing dialysis [ 7 , 29 , 30 , 31 ]. A healthy twin study reported that BMD was positively correlated with fat mass and lean mass, but the association was stronger with the latter [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreira et al (2014) recorded that aerobic exercise in excess of four‐times‐a‐week protected people against bone loss. Tønnesen et al (2016) found that BMD associated with physical activity in young adults was independent of both gender and vitamin D metabolite content in the body, and Jang et al (2016) added that physical activity simultaneously modified the amount of muscle and bone mass in the 20 to 49 age group.…”
Section: Discussionmentioning
confidence: 99%